The Relationship between Individual Characteristics and Safety Climate with Safety Behavior of Loading and Unloading Workers: A Study at Tenau Port, Kupang City, Indonesia - Idharsyah Termanu Dasi; Luh putu Ruliati; Anderias Umbu Roga; Jacob Matheos Ratu; Imelda Februati Ester Manurung (The Indonesian Institute of Science and Technology Research, 2026)
Occupational safety is a crucial aspect of loading and unloading activities at ports, which inherently carry high levels of risk. This study aimed to analyze the relationship between individual characteristics and safety climate with safety behavior among loading and unloading workers at Tenau Port, Kupang City. A quantitative study with a cross-sectional design was conducted among loading and unloading workers at Tenau Port. The study population consisted of all active workers registered in the TKBM Cooperative, and a sample of 73 respondents was selected using a random sampling technique. Data were collected using structured questionnaires and analyzed using Chi-Square and logistic regression tests. The results showed that most respondents had good individual characteristics (82.2%) and perceived a strong safety climate (74.0%). Bivariate analysis indicated a significant relationship between individual characteristics and safety behavior (p = 0.029) as well as between safety climate and safety behavior (p = 0.008). Multivariate analysis showed that safety climate was the most dominant factor associated with safety behavior (p = 0.038; Exp(B) = 5.312; 95% CI = 1.101–25.634). Workers who perceived a stronger safety climate were more likely to demonstrate compliant safety behavior than those who perceived a weaker safety climate. In conclusion, individual characteristics and safety climate were significantly associated with safety behavior among loading and unloading workers at Tenau Port, Kupang City. Strengthening workplace safety culture and improving workers’ competencies are recommended to enhance safety compliance.